Searching for Natural Gas Demand in the Next Decade - Bassam Fattouh; Anouk Honoré (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2017)
The expectation of an oversupplied gas market up to the mid-2020s has put natural gas demand back on the radar. This edition of the Oxford Energy Forum is dedicated to gas demand outlook in various regions of the world, with the starting point being the open question on whether, when, where and, eventually, at what price there will be sufficient demand to absorb the coming LNG wave. The first ten articles investigate the challenges and expectations for future gas demand in the main importing regions: Europe, Asia and South-East Asia, the MENA region and South America. Because it is difficult to draw common conclusions even at the regional level for diverse group of counties, authors provide separate views on key markets and there are three articles that specifically focus on Turkey, China and India. Following on from that, two articles consider the potential for new gas and LNG markets, with a focus on the particular case of the Ivory Coast and the role of FSRUs. The subsequent article focuses on the prospects for gas as a transport fuel as scarcely a day goes by without an announcement of new investments in shipping or refuelling facilities, or the conclusion of a cooperation agreement. Last but not least, the final article explores the relationship between coal and gas and what could be the key catalyst for coal-to-gas switching in the various regions.
Keywords: 330